Reading and Writing Instruction for Academically At-Risk Deaf and Hard of Hearing First-Year College Students. (January 2022) - Williams, Jessica; Sarchet, Thomastine; Walton, Dawn
Objective/Research Question: Students with disabilities, including deaf and hard of hearing (DHH) students, are enrolling in college at rates higher than in the past with most of them pursuing an associate's degree. For DHH students, their reading ability is a predictor of their academic achievement in college. However, more than half of DHH students enroll in remedial reading and writing college courses indicating they are not reading and writing at a college level and putting them at-risk for non-completion. In addition, remedial reading and writing courses often do not count for credit toward graduation and may hinder rather than support student progress. One way to mitigate the need for remedial coursework during college is to provide the remedial instruction in a low-stakes manner through summer bridge to college programs. The purpose of the present study was to measure the effects of remedial reading and writing instruction provided through a summer bridge program on first-year, academically at-risk DHH college students' ( N  = 20) reading and writing abilities.Methods: Using a pretest/posttest design, we implemented remedial reading and writing instruction for 2 hours a day, 5 days a week for 5 weeks.Results: Upon the completion of instruction, the student participants' reading and writing skills improved.Conclusions/Contributions: Our findings may encourage researchers to attempt remedial instruction through summer bridge programs with other populations with disabilities or English language learners.